next up previous
Next: Convolution filter Up: Mathematical Derivations Previous: Discretizing the Navier-Stokes-Equation

SOR update

Substituting $ c=\frac{a+b}{6a+2b} $, $ d=\frac{a}{6a+2b} $, $ e=\frac{b}{4(6a+2b)} $ we obtain:

$\displaystyle \left. \begin{array}{ll} \mathbf{p}= & \hat{\mathbf{f}}_{i,j,k}+c...
...athbf{v}^{(m+1)}_{i,j,k-1}+\mathbf{v}^{(m)}_{i,j,k+1}\right) \end{array}\right.$ (19)

Setting $ \mathbf{v}:=(r s t)^T $ we may write

\begin{displaymath}\begin{array}{ll} q_{x}=e & \left( s^{(m+1)}_{i-1,j-1,k}+s^{(...
...-s^{(m)}_{i,j-1,k+1}-s^{(m+1)}_{i,j+1,k-1}\right) , \end{array}\end{displaymath} (20)

hence for the residual vector

$\displaystyle \mathbf{r}_{i,j,k}=\omega \left( \mathbf{p}+\mathbf{q}-\mathbf{v}^{m}_{i,j,k}\right) ,$ (21)

and the SOR update of $ \mathbf{v}_{i,j,k} $ is given by

$\displaystyle \mathbf{v}^{(m+1)}_{i,j,k}=\mathbf{v}^{(m)}_{i,j,k}+\mathbf{r}_{i,j,k}.$ (22)



Gert Wollny 2003-03-17